Deregulation of SGK1 in Ulcerative Colitis: A Paradoxical Relationship Between Immune Cells and Colonic Epithelial Cells. Issue 9 (18th May 2018) - Spagnuolo, Rocco; Dattilo, Vincenzo; D'Antona, Lucia; Cosco, Cristina; Tallerico, Rossana; Ventura, Valeria; Conforti, Francesco; Camastra, Caterina; Mancina, Rosellina M; Catalogna, Giada; Cosco, Vincenzo; Iuliano, Rodolfo; et al.
Abstract: Background: Inflammatory bowel disease (IBD) is due to the interaction of genetic and environmental factors that trigger an unbalanced immune response ultimately resulting in the peculiar inflammatory reaction. Experimental models of IBD point to a role of T-cell-derived cytokines (Th17) and to SGK1 as mediator of the Th17 switch. We hypothesize that SGK1, a salt inducible kinase, directs lymphocytic behavior and tissue damage. Methods: Eleven controls and 32 ulcerative colitis (UC) patients were randomized according to endoscopic Mayo score. Mucosal biopsies from different intestinal tracts were analyzed by immunohistochemistry and quantitative real-time polymerase chain reaction to check the expression of disease markers including SGK1. Peripheral blood mononuclear cells (PBMCs) from patients and controls were analyzed by fluorescence-activated cell sorting. Finally, an in vitro cell model was developed to test the hypothesis. Results: SGK1 mRNA and protein expression in lesional areas of UC patients were lower than in normal peri-lesional areas of the same patients and in normal tissues of healthy controls. SGK1 expression was increased in PBMCs from UC patients, particularly in the CD4+ cell population, enriched in Th17 cells. IL17/IL13 was increased in patients and correlated with SGK1 expression. Genetically engineered Jurkat cells confirmed the effect of SGK1 overexpression on viability of RKO cells. Conclusions: These observations suggest a pathogenic mechanism whereby SGK1 overexpression in CD4+ T cells induces the secretion of the inflammatory cytokines IL17 and IL13, which downregulate the expression of SGK1 in target tissues. Our data suggest a novel hypothesis in the pathogenesis of UC, integrating colonic epithelial cells and lymphocytes.